Implementasi Logika Fuzzy untuk Pengukuran SoC Baterai Mobil Listrik yang Akurat - Muhammad Dzaky Ashidqi; Miftahul Anwar; Chico Hermanu B.A.; Agus Ramelan; Feri Adriyanto (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
Changes in temperature can affect the accuracy of the estimated SoC value based on voltage. In this study, fuzzy logic was implemented to correct the SoC estimation error caused by the influence of temperature. The system acquired data through sensors and then processed it using the Arduino microcontroller. Parameters in the form of voltage, temperature, and current were processed by Arduino with a fuzzy logic program which was uploaded into it and produced the output of the estimated SoC value. From the observations, it was found that the estimated SoC value from this method had better accuracy with a smaller error than the SoC estimation based on voltage alone. Using the RMSE method, the errors calculated in this method in the process of charging and discharging without running were 2.26 and 7.74, while the SoC estimation error based on voltage alone reached 4.88 and 12.8. In the discharging process with a running car, the SoC estimation results using fuzzy logic also showed accurate results. There was only 1% of SoC value increasing pattern during the discharging process, which the value trend should continue to decrease and should not be an increase. In addition, compared to the previous method applied to the same research object, namely the chemical equilibrium constant method, this method also showed more accurate results.